Quantitation of Surface-bound Proteins on Biochips Using MALDI-TOF MS - Lee, Juhee; Ryoo, Soo-Ryoon; Kim, Sang Kyung; Ahn, Joong-Hoon; Min, Dal-Hee; Yeo, Woon-Seok (JAPAN SOC ANALYTICAL CHEMISTRY, 2011)
We report on a novel method for the quantitation of proteins specifically bound on a ligand-presenting biochip by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS). The bound protein was digested by trypsin, and the resulting peptide fragments were analyzed by MALDI-TOF MS in the presence of an isotope-labeled internal standard (IS). The IS has the same sequence as a reference peptide (RP) of the target protein digest, but a different molecular weight. The absolute amount of the specifically bound protein on a biochip is then quantitated by comparison of mass intensities between the RP and the IS. Because they have the same molecular milieu, the mass intensities of these two analytes represent the real amounts of analytes on the chip. As a model system, we tested glutathione s-transferase (GST) and a GST-fusion protein, which were captured on glutathione-presenting biochips. We observed that the glutathione densities on biochips showed a good correlation with the absolute quantity of the proteins. We believe that our method will provide an alternative to currently existing tools for the absolute quantitation of surface-bound proteins.
Keywords: PLASMON RESONANCE; MASS-SPECTROMETRY; QUANTIFICATION; MICROARRAYS; ADSORPTION; CHIPS